Kajian Kritis Keputusan Mahasiswa Studi S-1 Fakultas Ekonomi Reguler Sore Usm - Endang Rusdianti; Sri Purwantini; Paulus Wardoyo (Universitas Semarang, 2017)
Higher education is a continuation of secondary education held to prepare learners to become members of the community who have academic and / or professional skills who can apply, develop and or create science of technology and or art. This research is designed as a qualitative research by using phenomenalisis and grounded approach. So that the phenomenon can be used as a study material on the factors that give rise to the interest and quality of service and the decision to choose the study program. As for the research partner as many as eight students active class regular afternoon. The results of this study resulted in two propositions of interest in continuing studies in universities and service quality in universities. Each proposition comes with a picture of the theory building. Which ultimately led to the theoretical model of the decision to continue the study which is a study for further empirical research.